Real-time simulation of multibody systems with hydraulic actuators - Ferreira, José (2024)
[Excerpt] Hydraulic actuators are extensively utilized in many engineering applications, such as robotic arms and heavy machinery, due to their high-power density, precise control, high force output, and reliability. As automation and artificial intelligence (AI) become increasingly prevalent in the industry, a good number of systems operate autonomously with the aid of AI. Consequently, real-time simulation environments have become indispensable for the development and testing of autonomous and AI systems, which is paramount for ensuring the reliable and safe operation of those systems. Thus, in this work, the process of modeling of mechanical systems with hydraulic actuators with real-time features is presented and formulated under the framework of multibody dynamics tools.